Korean Toddlers at Play or at Work? Commodifiable Authenticity of Sponsored Child-Rearing Vlogs - Hanwool Choe (Social Media + Society)
As child-rearing everyday vlogs grow in popularity in South Korea, children featured in these vlogs are increasingly becoming influencers. Through a case study of sponsored everyday vlogs of a 3-year-old Korean toddler, I identify two strategies that transform the toddler’s everyday life into a marketplace: The toddler’s (1) pretend play as product demonstration and actual use and (2) image-making for branding. These strategies construct the toddler as a marketer promoting sponsored products and brands to adult consumers, while simultaneously offering virtual experiences of everyday family lives that viewers can vicariously engage with. This phenomenon, I argue, creates “commodifiable authenticity.” Troubling the boundary between child play and influencer work, commodifiable authenticity shapes and reinforces the broader discourse of “child-as-commodity.” Ultimately, my examination illuminates how by repackaging marriage and family life as media entertainment, Korean child-rearing vlogs hold new cultural significance considering that South Korea has the lowest fertility rate in the world.